Diverse Sexual Behaviors in Undergraduate Students: Findings From a Campus Probability Survey. Issue 6 (18th May 2021) - Herbenick, Debby; Patterson, Callie; Beckmeyer, Jonathon; Gonzalez, Yael R. Rosenstock; Luetke, Maya; Guerra-Reyes, Lucia; Eastman-Mueller, Heather; Valdivia, Dubravka Svetina; Rosenberg, Molly
ABSTRACT: Background: Probability-based surveys of college students typically assess sexual behaviors such as oral, vaginal, and anal sex. Little is known about the broader range of sexual behaviors in which students engage. Aims: In a random sample survey of undergraduate students, we aimed to: (1) describe how recently participants had engaged in solo and partnered sexual behaviors, (2) examine how frequently participants enacted certain rough sex sexual behaviors (e.g., light spanking, hard spanking, choking, slapping, and others), (3) assess participants' frequency of experiencing certain rough sex behaviors, (4) describe participants' frequency of threesome/group sex, (5) assess the characteristics of participants' experiences with choking during sex; and (6) examine choking and face slapping in regard to consent. Methods: A confidential, online cross-sectional survey of 4, 989 randomly sampled undergraduate students at a large U.S. university. Outcomes: Participants reported having engaged in a broad range of solo and partnered sexual activities, including rough sex behaviors. RESULTS: The most prevalent general sexual behaviors were solo masturbation (88.6%), oral sex (79.4% received, 78.4% performed), penile-vaginal intercourse (73.5%), and partnered masturbation (71.1%). Anal intercourse was the least prevalent of these behaviors (16.8% received, 25.3% performed). Among those with any partnered sexual experience, 43.0% had choked a partner, 47.3% had been choked, 59.1% had been lightly spanked and 12.1% had been slapped on the face during sex. Clinical translation: College health clinicians and educators need to be aware of the diverse and evolving range of solo and partnered sexual behaviors reported by students. In addition to counseling students about pregnancy and sexually transmitted infection risk, clinicians might assess patients' engagement in diverse sexual behaviors, such as choking/strangulation during sex, given the risk for serious outcomes including death. Strengths and limitations: Strengths of our research include the large sample size, use of random sampling, high response rate for college populations, broad range of behaviors assessed, and novel data on choking during sex. Among our limitations, we did not assess to what extent the experiences were wanted, pleasurable, or appealing to participants. Except for in relation to choking and slapping, we also did not assess issues of consent. CONCLUSION: Participants reported engaging in diverse sexual behaviors, some of which have important clinical implications, are understudied, and warrant further research.